Comparison between thermal ablation and surgery in low risk papillary thyroid carcinoma: a prospective study - Gong, Wenbo; Zhang, Runfang; Zhang, Songtao; Zhai, Yifei; Zheng, Chen; Zhang, Dongyan (Frontiers in Endocrinology, 2024)
Objective: To conduct a comparative analysis of the efficacy, safety, and impact on quality of life outcomes between thermal ablation and surgical interventions in patients diagnosed with papillary thyroid carcinoma (PTC).Methods: A prospective study was undertaken, enrolling patients with PTC ≤5mm who underwent radiofrequency ablation (RFA), laser ablation (LA), or surgery, for analysis of efficacy and safety outcomes. The Thyroid Cancer-Specific Quality of Life questionnaire was administered to all patients before treatment and at 3, 6, and 12 months post-treatment.Results: A total of 162 eligible patients were included in the study. Major complications were not observed in the RFA and LA groups, while five cases were reported in the surgery group, although no statistically significant differences were observed. Minor complications were documented in two, three, and 14 patients in the RFA, LA, and surgery groups, respectively, with no significant variances noted. Surgical duration and hospitalization time were notably shorter in the thermal ablation groups. At the final follow-up, complete disappearance of nodules was seen in 71.4% of cases treated with RFA and 71.0% of cases managed with LA, with no significant disparities between the groups. Both RFA and LA exhibited similar effects on quality of life, with thermal ablation techniques showing better functional outcomes in comparison to surgery. Across all groups, adverse effects were most pronounced at the 3-month post-treatment mark but gradually reverted to baseline levels in the thermal ablation group, contrasting with the surgery group.For PTC ≤5mm, both RFA and LA exhibited similar cancer control outcomes and superior quality of life on par with surgery, while minimizing complications. These findings underscore the promise of RFA and LA as potential standard treatments for small PTCs, subject to further confirmation in future studies.